Pretreatment hemoglobin, myeloma subtype, and induction regimens as independent prognostic factors for survival after autologous stem cell transplantation in multiple myeloma: a retrospective cohort study - Zhang, Yong; Yang, Guangzhong; Gao, Wen; Chen, Wenming (Hematology (Luxembourg), 2025)
Autologous hematopoietic stem cell transplantation (auto-HSCT) is standard for eligible multiple myeloma (MM) patients, yet outcomes are heterogeneous. Besides established markers like cytogenetics and ISS, the independent prognostic value of pretreatment hemoglobin (Hb), myeloma subtype, and induction regimen requires clarification. This study aimed to assess these factors to improve risk stratification. We retrospectively analyzed 350 MM patients undergoing first auto-HSCT at Beijing Chao-Yang Hospital (2001-2019). The impact of baseline Hb (<10 vs. ≥10 g/dL), subtype (IgG vs. non-IgG), and induction regimen (bortezomib-based vs. others) on progression-free survival (PFS) and overall survival (OS) was evaluated using Kaplan-Meier and Cox regression. With a median follow-up of 58 months, median PFS and OS were 42 months (95% CI 36-48) and 98 months (95% CI 83-113), respectively. Multivariate analysis identified three independent predictors of superior PFS: Hb ≥10 g/dL (HR = 0.65, = 0.012), IgG subtype (HR = 0.72, = 0.018), and bortezomib-based induction (HR = 0.58, = 0.004). Attaining CR/VGPR post-transplant also significantly prolonged PFS versus PR or less (median 55 vs. 37 months, = 0.044). Pretreatment hemoglobin, IgG subtype, and bortezomib-based induction are independent predictors of survival after auto-HSCT. Hb, a simple and widely available marker, adds prognostic value beyond ISS and cytogenetics. Integrating these factors into prognostic models can help tailor therapy and improve patient management.